Performance of Catla catla (Ham.) fingerlings fed with carbohydrate-rich diets in manured tanks - Manjappa, K. (2021)
This study was undertaken to examine the level to which dietary fish meal could be reduced, replacing it with maize, a locally available, cheap carbohydrate source and to study the protein sparing effect of carbohydrate in catla (Catla catla), grown in manured tanks. Twelve mud bottomed cement tanks of 18 m2 (6m x 3m x 1m) each, fertilized initially with poultry manure at 2000 kg•ha-1 (3.6 kg per tank) were used. The tanks were subsequently fertilized with poultry manure at 5% of the initial dose at fortnightly intervals. Four diets viz. T0, T1, T2 and T3 containing 0, 10, 20 and 30% fish meal were formulated. Catla fingerlings (av. wt. 1.9 g) stocked at 1 fish•m-2 received the diets provided in plastic trays at 5% body weight once daily in the morning hours for 120 days. The diets contained 18.47, 23.51, 27.78, 31.98% crude protein and 54.48, 46.06, 40.84, 33.89% carbohydrate (NFE), respectively. The highest and lowest growths of fish were obtained with diets T1 and T0; fish fed fish meal containing diets exhibited significantly higher growth. FCR in the different treatments was statistically non-significant (P>0.05). PER improved with decreasing dietary protein and increasing carbohydrate. Fish survival ranged from 92.59 to 98.14%. Diets influenced carcass composition and digestive enzyme activity. A significant increase in lipid deposition was recorded with increasing dietary carbohydrate content. A positive relationship was recorded between hepatopancreatic amylase activity and dietary carbohydrate level, while intestinal protease activity was inversely related. Lipase activity was comparatively lower in all the treatments. The ability of catla to utilize higher levels of carbohydrate, the protein sparing effect of carbohydrate and the economic implications of reducing dietary fish meal content are discussed.